Caracterización genética de cuatro poblaciones de ovinos criollos de Argentina - Peña, Sabrina (2017)
Creole sheep are the founders of sheep farming in Argentina and have contributed in a sustained way to the economic, social and cultural development of some regions of this country. However, it is a scarcely valorised and poorly studied genetic resource. In order to genetically characterize the Argentinian Creole sheep, DNA samples were taken from four representative populations located in the provinces of Buenos Aires, Corrientes, Santiago del Estero and Salta. These flocks were selected because they are considered to be conserved groups, they have the phenotypic characteristics of the creole breed and there are no records about the introduction of animals of other breeds into those systems. A total of 30 microsatellites and the D-loop region of mitochondrial DNA were analysed. Microsatellite analysis showed high level of genetic diversity within populations (Ho= 0.676; He= 0.685; PIC= 0.713). This variability is explained by differences between molecular patterns of the studied individuals, which can be classified into three significantly different population groups: BA, SA, SE+CO. Since these populations explain very little of the total variability (7.6%), it can be considered that they belong to a same race. The analysis of the mitochondrial D-loop showed that Argentinian Creole sheep have haplotypes belonging to the Asian haplogroup, which is widely distributed in the Spanish breeds, which are considered to be their ancestors. The results obtained in the present study will provide information to develop management criteria for this genetic resource in Argentina, in order to implement their conservation, recovery and/or to develop breeding programs.